Counselling portal: AskAkak.com / Khairiah Rahmat - Khairiah , Rahmat (2003)
We have reached the beginning of a new millennium, and needless to say, information technology is relatively changing very rapidly Along with this revolution, the lives of people have become more complex and convoluted, with problems and insecurities creeping up endlessly.Traditional face-to-face counselling does not prove to be the best remedy for this phenomenon anymore. Living at a fast pace has forced people to turn technology to provide them with the best solution for solving their problems and soothing their troubled mind-online counselling. Online counselling has brought us into a new world of communication and problem solving. Ironically computer counselling has already evolved before web has taken its roots. Initial is was more on program which counsels and acts like educators. When web evolved, online counselling was introduced due to the fact that there were numerous available mediums for communication and counselling. More people who knew the web week started experimenting on this medium for communication and counselling.Well we are not pioneer , but we will try to carry on from where others have already reached. The system that we are going to build is called the counselling Portal. Although this portal is built on the platform of existing knowledge and ideas, its attempts to address three different issues simultaneously,"the issues of academic, career and relationship. These three issues were selected among all others because of the inherent fact that they are the most mind-boggling problems that students today have to face. With the aim of building an elegant yet versatile portal in mind, we will try to select the best resource and information we could find. We hope to cater not only the current needs of students, bur also their wants in the long run. Which is why we are using the latest web technology-PHP.